Efficient Electron Transfer Processes and Enhanced Electrocatalytic Activity of Cobalt(II) Porphyrin Anchored on Graphene Oxide. Issue 2 (22nd June 2015) - Cho, Sung; Lim, Jong Min; You, Jung‐Min; Jeon, Seungwon; Kim, Dongho
Abstract: We investigated the electronic perturbation between graphene oxide and cobalt porphyrin to reveal the origin of the enhanced electrocatalytic activity of a hybrid complex using time‐resolved spectroscopic measurements and theoretical calculations. The impulsively generated charge‐separated state, GO − ‐(Co II APFP) +, undergoes fast charge recombination (<10 ps) between GO − and (Co II APFP) + moieties. This fast charge recombination is directly related to the quick neutralization of (Co II APFP) +, which shortens the dead time of inactive Co III APFP after the electrocatalytic reduction reaction. The fast transformation of inactive Co III APFP to active Co II APFP is an important factor in the enhanced electrocatalytic activity of the hybrid complex. Abstract :